CONNECTING THE DOTS: INVESTIGATING THE RELATIONSHIP BETWEEN HBA1C AND LIPID PROFILE - JOSEPH KI; SIVAGAMI K; MOHAN KUMAR; APARNAVI P; JEEVITHAN S (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: To determine the association between lipd profile and HbA1c. Hemoglobin A1c (HbA1c) is used to monitor blood sugar levels. HbA1c is one among the panel of tests that is done for patients who come for routine master health check-ups. This helps us to identify pre-diabetic and diabetic individuals. Diabetic individuals are at increased risk for dyslipidemia. The aim of this study is to look into the association between lipid profile and HbA1c. Methodology: This study was done in a multispecialty hospital in the Western part of Tamil Nadu among the patients who came for master health check-ups between 2017 and 2024. Ethical Committee approval was obtained (EC/AP/1100/12/2023). From the laboratory database of 67,000 patients, patients who reported for the 1st time and had their HbA1c and lipid profile levels evaluated were selected. They were categorized into normal, pre-diabetic, and diabetic based on HbA1c values. Data were analyzed using the Statistical Package for Social Sciences 27. Categorical variables were expressed as frequency and percentages whereas continuous variables were expressed as mean and standard deviation. Analysis of variance (ANOVA) was used to find if there was a significant difference in lipid profile among the three groups. Results: Our study had 23,238 participants. Out of them 7168 (30.84%) had normal HbA1c levels, 8347 (35.91%) were pre-diabetics, and 7955 (34.23%) were diabetic patients. The mean total cholesterol (TC) level (186.8±40.14) and low-density lipoprotein (LDL) cholesterol level (129.74±37.20). It was high for pre-diabetic patients. The median very LDL (VLDL) cholesterol (29.00(21–39) levels were higher for diabetic patients. The mean high-density lipoprotein (HDL) cholesterol levels (39.54±9.40) were less for diabetic patients. One-way ANOVA revealed a significant difference in TC, HDL cholesterol, LDL cholesterol, and VLDL cholesterol levels between the three groups. Pearson correlation coefficient showed a positive correlation between VLDL, LDL, TC, and HbA1c. HbA1c and HDL cholesterol were negatively correlated. Conclusion: Our study revealed a significant correlation between HbA1c and these changes signify a higher risk of cardiovascular complications in individuals with diabetes mellitus. Understanding these associations underscores the need for vigilant monitoring and proactive management of lipid profiles among pre-diabetics and diabetics to reduce the risk of cardiovascular diseases and enhance their overall health.